2012
DOI: 10.1093/nar/gks593
|View full text |Cite
|
Sign up to set email alerts
|

The wobble nucleotide-excising anticodon nuclease RloC is governed by the zinc-hook and DNA-dependent ATPase of its Rad50-like region

Abstract: The conserved bacterial anticodon nuclease (ACNase) RloC and its phage-excluding homolog PrrC comprise respective ABC-adenosine triphosphatase (ATPase) and ACNase N- and C-domains but differ in three key attributes. First, prrC is always linked to an ACNase silencing, DNA restriction–modification (R–M) locus while rloC rarely features such linkage. Second, RloC excises its substrate’s wobble nucleotide, a lesion expected to impede damage reversal by phage transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…The cleavage of tRNA Lys inhibits the host translation and as a consequence the reproduction of the T4 phage. The RloC enzyme that is homologous to PrrC does not seem to be linked to R-M systems, has similar biochemical properties and is activated under genotoxic stress (52,53). Recent analysis has shown that the ACNase domain of both proteins belongs to the HEPN superfamily that is merging as a major group of ribonucleases that are involved in various forms of defense and stress response (54,55).…”
Section: Defense Mechanisms In Bacteria and Archaeamentioning
confidence: 99%
“…The cleavage of tRNA Lys inhibits the host translation and as a consequence the reproduction of the T4 phage. The RloC enzyme that is homologous to PrrC does not seem to be linked to R-M systems, has similar biochemical properties and is activated under genotoxic stress (52,53). Recent analysis has shown that the ACNase domain of both proteins belongs to the HEPN superfamily that is merging as a major group of ribonucleases that are involved in various forms of defense and stress response (54,55).…”
Section: Defense Mechanisms In Bacteria and Archaeamentioning
confidence: 99%
“…Structural studies on RAMPs have demonstrated that these independently acquired histidines and other polar residues might constitute distinct but catalytically equivalent active sites for this RNase superfamily [66,68]. Like the BECR RNases, the HEPN and RAMPs are also metal-independent endoRNases that generate products with cyclic 2’-3’ ends [64-66]. Metal-dependent active sites require a precise 3D configuration of metal-chelating residues coming from different parts of the fold probably making them harder to reconfigure.…”
Section: Reorganization Of Active Site Residues While Retaining Ancesmentioning
confidence: 99%
“…The ACNase RloC that is homologous to PrrC, although usually not linked directly to RM systems, seems to function under the same logic, i.e. as an antiviral contingency that acts when DNA restriction is alleviated under genotoxic stress [32,33]. Although PrrC and RloC are not known to cause bacterial suicide or persistence, they clearly function on the exact same principle, namely inhibiting translation to prevent virus reproduction in situations when an innate anti-phage immunity mechanism fails.…”
Section: Introductionmentioning
confidence: 99%